2016
DOI: 10.1152/jn.00961.2015
|View full text |Cite
|
Sign up to set email alerts
|

Microstimulation of the lumbar DRG recruits primary afferent neurons in localized regions of lower limb

Abstract: Ayers CA, Fisher LE, Gaunt RA, Weber DJ. Microstimulation of the lumbar DRG recruits primary afferent neurons in localized regions of lower limb. J Neurophysiol 116: 51-60, 2016. First published April 6, 2016 doi:10.1152/jn.00961.2015.-Patterned microstimulation of the dorsal root ganglion (DRG) has been proposed as a method for delivering tactile and proprioceptive feedback to amputees. Previous studies demonstrated that large-and mediumdiameter afferent neurons could be recruited separately, even several mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Therefore, we used stimulus-triggered averaging to detect responses evoked by stimulation. The presence of a compound action potential on each nerve was determined by comparing responses following stimulation to baseline recordings in which no stimulation occurred, using a previously-published method 67,68 . To determine the response detection threshold, we calculated the 99% confidence interval on the root mean squared baseline amplitude.…”
Section: Compound Action Potential Detectionmentioning
confidence: 99%
“…Therefore, we used stimulus-triggered averaging to detect responses evoked by stimulation. The presence of a compound action potential on each nerve was determined by comparing responses following stimulation to baseline recordings in which no stimulation occurred, using a previously-published method 67,68 . To determine the response detection threshold, we calculated the 99% confidence interval on the root mean squared baseline amplitude.…”
Section: Compound Action Potential Detectionmentioning
confidence: 99%
“…While most studies have used penetrating electrode arrays to record from neurons in the interior of the DRG, recent work has demonstrated that afferent signals can be recorded from neurons near the exterior of DRG using surface recording arrays (Kashkoush, Gaunt, Fisher, Bruns, & Weber, 2019;Sperry et al, 2018) and that microelectrodes can be used for low-current microstimulation of DRG neurons (Ayers, Fisher, Gaunt, & Weber, 2016;Bruns, Weber, & Gaunt, 2015;Fisher et al, 2014). Additionally, dorsal root ganglion stimulation (DRGS) is an emerging therapy for chronic neuropathic pain (Deer et al, 2017), providing a non-addictive alternative to opioids for pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple research groups are working to augment prosthetic hands with naturalistic sensation, delivered via electrical stimulation applied directly to the peripheral nerves [1318], spinal cord [19], or cortex [20]. Electrical stimulation can produce tactile and proprioceptive sensations referred to the phantom hand and limb.…”
Section: Introductionmentioning
confidence: 99%